1982
DOI: 10.1080/09670878209370676
|View full text |Cite
|
Sign up to set email alerts
|

Grafting—A simple technique for overcoming bacterial wilt in tomato

Abstract: Experimental and commercial results are given of work on bacterial wilt (Pseudomonas solanacearum (E. F. Smith) E. F. Smith) in tomato. The use of resistant cultivars and a grafting technique was investigated. Resistant cultivars from Malaysia, Philippines and the USA were tested but no satisfactory results were obtained. The simple grafting technique overcame the disease in the hot wet climate of Brunei. The best stock donor found was Solarium torvum, while best quality fruits consistent with good yields were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Grafting has been utilized to manage bacterial wilt in tomato crops worldwide (11,24,25,30,39), and has been proposed recently in the United States for open-field and high-tunnel production (22,33). Breeding lines CRA 66 and Hawaii 7996 were found to significantly reduce bacterial wilt incidence in naturally infested soils in North Carolina (33).…”
mentioning
confidence: 99%
“…Grafting has been utilized to manage bacterial wilt in tomato crops worldwide (11,24,25,30,39), and has been proposed recently in the United States for open-field and high-tunnel production (22,33). Breeding lines CRA 66 and Hawaii 7996 were found to significantly reduce bacterial wilt incidence in naturally infested soils in North Carolina (33).…”
mentioning
confidence: 99%
“…Several studies have shown that S. torvum has high levels of resistance towards pests, nematodes and pathogens (Collonnier et al, 2003;Clain et al, 2004;Gousset et al, 2005). It has been used as a rootstock for the grafting of susceptible tomato and eggplant varieties (Peregrine and Ahmad, 1982;Singh and Gopalakrishnan, 1997). Moreover, interspecific crosses between plant species are an ideal way for introducing desirable genetic traits in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…This disease, if not controlled, may result in the death of all plants in a specific sowing in soils where some years of continuous cropping has taken place; fields may need to be excluded from the production of solanaceous crops (Rivard et al 2012). In studies conducted in Brunei, Peregrine and Ahmad (1982) demonstrated effective control of this disease with tomato varieties such as Roma grafted onto S. torvum rootstocks. Thirty years later, Cardoso et al (2012) Lin et al (1998) evaluated two popular local tomato cultivars, Farmers 301, susceptible to bacterial wilt, and Taichung ASVEG No.…”
Section: Bacterial Wilt Controlmentioning
confidence: 98%
“…The use of grafting as a means to control bacterial wilt (R. solanacearum) is long established (Peregrine & Ahmad 1982). The pathogen has a wide host range and maintains considerable diversity worldwide.…”
Section: Bacterial Wilt Controlmentioning
confidence: 99%
See 1 more Smart Citation